2005
DOI: 10.2217/17455057.1.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in Inflammatory Bowel Disease

Abstract: Crohn's disease and ulcerative colitis are two chronic inflammatory conditions involving the gastrointestinal tract. While many aspects of the management of these diseases are identical for all patients, there are some issues specific to women that are not necessarily part of routine care. Certain gender-specific issues such as menses, fertility, pregnancy and menopause are often overlooked and mismanaged. Women have different psychologic concerns compared with men in regard to their self-image and impact of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although it has been anecdotally reported that IBD symptoms decrease after menopause, only one‐third of the post‐menopausal IBD respondents confirmed that their IBD symptoms improved following cessation of menses, with the majority indicating no change. Kane and Reddy reported that hormone replacement therapy was associated with a lower likelihood of flare and less severe symptoms in a flare for a sample of post menopausal women with IBD .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although it has been anecdotally reported that IBD symptoms decrease after menopause, only one‐third of the post‐menopausal IBD respondents confirmed that their IBD symptoms improved following cessation of menses, with the majority indicating no change. Kane and Reddy reported that hormone replacement therapy was associated with a lower likelihood of flare and less severe symptoms in a flare for a sample of post menopausal women with IBD .…”
Section: Discussionmentioning
confidence: 96%
“…A recent systematic review indicated that women with IBS had increased gastrointestinal symptoms during their menses . In inflammatory bowel disease (IBD), there is a perception that women experience a change in gastrointestinal symptoms during menses, much of it based on small studies . However, there are limited data on the nature of gastrointestinal symptoms during and around menses even in healthy women without IBD or other gastrointestinal disease, hence it is difficult to draw causal conclusions without larger, controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…16 General patterns of nonadherence include under-or overconsuming medication, failing to fill a prescription, taking doses at inappropriate intervals, and administering medication incorrectly. 16,17 By comparing patients' medication bottles and reported use with the outpatient records of 5 cardiologists and 2 internists, Bedell et al found medication discrepancies in 239 of 312 (76%) patients. 18 While more than half (51%) of the 545 discrepancies resulted from patients taking medications that were not recorded, 29% were due to patients not taking a recorded medication and 20% were due to differences in dosage.…”
Section: ■■ Defining Adherence and Persistencementioning
confidence: 99%
“…The importance of adherence has been explored previously [8][9][10][11][12][13]. However, despite the expected benefits, between 40 and 60% of patients with UC do not take their oral 5-ASA medication as prescribed [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%